Vanname Shrimp Health Monitoring System Using Internet of Things-based Image Processing Method - Ummul Khoiriyah; Herry Sufyan Hadi; Putri Yeni Aisyah (Institut Teknologi Sepuluh Nopember, 2022)
Viruses are known to have attacked vaname shrimp, shrimp infected with the virus showed several abnormal things, including the appearance of a reddish color on the shrimp's body, and redness on the shrimp's tail. In healthy Vannamei Shrimp, the shrimp body shows a brownish color, and there is no reddish color on the tail and body of the shrimp. Implementation of a prototype of a shrimp health monitoring system needs to be done to determine the health condition of shrimp. This final project will produce a prototype that can monitor shrimp health, by adopting Artificial Intelligent (AI) learning technology for image processing and recognition. Presenting a prototype consisting of hardware and software analysis of healthy Vannamei shrimp for the purpose of monitoring the health of Vannamei shrimp thereby increasing the productivity of the Internet of Things (IoT) based ponds.